Efficacy and safety of dorzagliatin for type 2 diabetes mellitus: A meta-analysis and trial sequential analysis - Yu, Yunfeng; Yang, Xingyu; Tong, Keke; Yin, Shuang; Hu, Gang; Zhang, Fei; Jiang, Pengfei; Zhou, Manli; Jian, Weixiong (Frontiers in Cardiovascular Medicine, 2022)
Abstract: Objective: To evaluate the efficacy and safety of dorzagliatin in the treatment of type 2 diabetes mellitus(T2DM) by using meta-analysis and trial sequential analysis(TSA). Method: Search for clinical trials of dorzagliatin for T2DM in eight databases, with a time limit of build to July 2022. The included studies that met the requirements were carried out for meta-analysis and TSA. Results: In terms of efficacy endpoints, meta-analysis showed that dorzagliatin decreased glycated hemoglobin A1c(HbA1c) (mean difference(MD)-0.65%, 95% confidence interval(CI) -0.76 -0.54, P<0.00001), fasting plasma glucose(FPG)(MD -9.22mg/dL, 95%CI -9.99 -8.44, P<0.00001), 2h postprandial glucose(2h-PPG)(MD -48.70mg/dL, 95%CI -55.45 -41.96, P<0.00001), homeostasis model assessment 2 of insulin resistance(HOMA2-IR)(MD -0.07, 95%CI -0.14 -0.01, P=0.03) and increased homeostasis model assessment 2 of ß-cells function(HOMA2-β)(MD 2.69, 95%CI 1.06 4.31, P=0.001) compared with placebo. And TSA revealed that the benefits observed for the current information set were conclusive, except for HOMA2-IR. In comparison with placebo, dorzagliatin increased triglyceride(TG)(MD 0.43mmol/L, 95%CI 0.30 0.56, P<0.00001),total cholesterol(TC)(MD 0.13mmol/L, 95%CI 0.05 0.21, P=0.001), body weight (MD 0.38kg, 95% CI 0.12-0.63, P=0.004) and body mass index(BMI)(MD 0.14kg/m2, 95% CI 0.05-0.24, P=0.003), while low density lipoprotein cholesterol(LDL-C), high-density lipoprotein cholesterol(HDL-C), systolic blood pressure(SBP) and diastolic blood pressure(DBP) were comparable. And TSA demonstrated that TG, TC, body weight, and BMI were conclusive. In terms of safety endpoints, dorzagliatin increased total adverse events(AEs)( risk ratio(RR) 1.56, 95%CI 1.06 2.30, P=0.03), while serious AEs, hyperlipidemia and hypoglycaemia were all comparable. And TSA indicated that the results need to be confirmed by additional studies. Harbord regression showed no publication bias. Conclusion: Dorzagliatin was effective in lowering glycemia, reducing insulin resistance and improving islet ß-cells function without affecting blood pressure, LDL-C and HDL-C. Although dorzagliatin caused a mild increase in TG and TC, it did not increase the incidence of hyperlipidemia, and the small increases in body weight and BMI were not clinically significant enough. In terms of safety, the total AEs caused by dorzagliatin may be a cumulative effect of single AEs, with no drug-related adverse event being reported at a higher incidence than placebo alone. Dorzagliatin's serious AEs, hyperlipidemia, and hypoglycemia are comparable to that of placebo, and dorzagliatin has a good safety profile.